The benefits of scuba diving for people with physical disabilities: a systematic review of the literature - Guntur, Guntur; Solikhin, Muhamad Nanang; Fauzi, Fauzi; Bin Shahril, Mohd Izwan; Salimin, Norkhalid Bin (Universitas Negeri Yogyakarta, 2023)
The purpose of this study was to find out other benefits of scuba diving for persons with physical disabilities through a systematic literature review. The technique used in this research is a literature study. The literature analysis used the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method. A total of seven articles were selected for review. A review of articles shows that diving can be treated as a multidimensional therapy in water, allowing people with and without disabilities to share activities together. Such rehabilitation involves comprehensive stimulation of the human body through social interaction through participation in class, influencing the mental and physical environment to regain awareness of one's own body and the movements one can perform, to feel one's own body position and the possibility of providing direction of motion and the benefits of increasing self-reliance in water. Utilization the aquatic environment allows muscle relaxation, which, as a result, can have a positive effect on spasticity and often increase the very limited range of motion of joints in a natural environment allowing increased movement and coordination in a much easier manner than in a terrestrial environment. A person who scuba dives could learn and demonstrate independence by keeping himself safe, as well as the safety of his colleagues. Diving encourages a person to spend time with other people and, as such, provides an opportunity to be in a group whose members include people without disabilities, as well as people with locomotor system dysfunction, providing a sense of affiliation with the group and responsibility for it. members and create a positive mental state.